(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
The article analyzes the problem of congestion of transport hubs closest to the agglomerations. The reason for this problem is usually the slow development of the transport system with the rapid growth of population in satellite cities. Foreign experience in ensuring transport accessibility of agglomerations has been studied. A solution to the problem under consideration with the help of rail transport is proposed (using the example of St. Petersburg, the extension of the Moscow-Petrograd metro line to Pushkin). The results obtained can be used to improve planning for the development of transport systems of agglomerations.